A Quantitative Framework for Task Allocation in Distributed Agile Software Development - Aslam, Waqar; Ijaz, Farah (IEEE access, 2018)
Distributed agile software development is a promising paradigm, addressing the necessities of emergent software application markets that are described by huge user base and small time to market characteristics. A key decision involved during the development process, is task allocation to team members. An appropriate task-member assignment facilitates project management, lessens the complexities and influences chances of project success. Task allocation becomes a more challenging activity in a distributed agile software development due to insufficient understanding of different factors and dependencies involved. We propose a task allocation framework comprising of two phases: one, identifying factors and dependencies that strongly influence the task allocation decision; two, proposing a quantitative method that allocates tasks to team members who best match the task requirements. Task requirements are expressed as capabilities, catering for different aspects, such as technical, personal, and environment. Our method stays transparent to the targeted objectives, in this case the best match. Other objectives, such as quality and cost may be introduced conveniently; even multiple objectives can be addressed. Such a method also allows quality evaluation of task-member assignment during and after the project completion, toward minimizing related risks.